Estrategias de branding para el posicionamiento de la empresa “Medicina Natural” en la ciudad de Ambato - Asqui Chugchilan, Pamela Nicole (2023)
This study focuses on the development of branding strategies to improve the positioning of the company Medicina Natural in the city of Ambato. The overall objective is to propose effective branding actions, based on a comprehensive market analysis, to strengthen brand perception among local consumers. To achieve this objective, a detailed analysis of the competition, consumer behavior and market trends in the natural medicine sector in the city will be carried out. Based on the findings, creative and distinctive strategies will be designed to highlight the company's unique attributes and build an emotional connection with consumers. By implementing these strategies, Medicina Natural will be able to consolidate its position in the Ambato market and achieve a sustainable competitive advantage